The Importance of Ocean Science Diplomacy for Ocean Affairs, Global Sustainability, and the UN Decade of Ocean Science - Polejack, Andrei (Frontiers in Marine Science, 2021)
The ocean is highly impacted by human activities, and ambitious levels of science are urgently needed to support decision making in order to achieve sustainability. Due to the high cost and risk associated with ocean exploration and monitoring in time and space, vast areas of the oceanic social ecological system remain under-sampled or unknown. Governments have recognized that no single nation can on its own fill these scientific knowledge gaps, and this has led to a number of agreements to support international scientific collaboration and the exchange of information and capacity. This paper reviews current discussions on ocean science diplomacy, i.e., the intersection of science with international ocean affairs. Ocean science is intrinsically connected with diplomacy in supporting negotiations toward a more sustainable future. Diplomacy supports essential aspects of scientific work such as capacity building, technology and information/knowledge exchange, and access and sharing of research platforms. Ocean science diplomacy underlies the work of many intergovernmental organizations that provide scientific guidance, such as the Intergovernmental Oceanographic Commission (IOC), the Intergovernmental Panel on Climate Change (IPCC), and the International Council for the Exploration of the Sea (ICES), and United Nations Convention on the Law of the Sea (UNCLOS). To illustrate how critical science diplomacy is to global ocean affairs, this paper examines examples of the influence of ocean science diplomacy in UNCLOS. Furthermore, this paper discusses the utility of ocean science diplomacy in support of the UN 2030 agenda, and the UN Decade of Ocean Science.